Research of procrastination in connection with students’ personal characteristics (on the example of Kazakhstan) - I. K. Kairatova; S. K. Kudaibergenova (Хабаршы. Психология және социология сериясы, 2019)
The student's age is the important period in human life during which he/she decides on the professional choice, finds feelings of maturity and identity, plans the future. Educational and professional achievements which strengthen self-confidence and the ability to productive activity are significant, and at the same time put base for successful self-realization in the future. However procrastination at which the person postpones until the moment of "deadline" the most important and modern issues and tasks and also decision-making can become an obstacle for such achievements. Negative consequences are expressed not only in depression of success and efficiency of the person and an obstacle of her development, both in educational, and in professional medium, but also in acute emotional experiences of own failure, sense of guilt, dissatisfaction with results of the activity. The problem of procrastination is investigated in domestic science quite recently, and there are practically no unambiguously established reasons causing predilection "to put away for later". In this regard there are questions that influences developing of procrastination at students whether personal characteristics of students are bound to it. This research is referred on finding answers to the matters.